Legal and Regulatory Complexities in the Governance of Indonesian Migrant Worker Deployment: The Role of BP3MI in Overseas Worker Deployment - Ridwan Haris; Vallencia Nandya Paramita; M. Syahrul Borman (Penerbit Goodwood, 2026)
Purpose: This study examines the legal and regulatory complexities surrounding the overseas departure process of Indonesian Migrant Workers (PMI), focusing on the pre-departure phase of migration governance and the role of the Indonesian Migrant Worker Protection Agency (BP3MI).Research Methodology: A qualitative normative-empirical legal approach was employed. Primary data were collected through indepth interviews with 25 informants, including BP3MI officials, representatives of licensed placement agencies (P3MI), legal aid practitioners, and migrant worker advocates. Secondary data were obtained from court decisions, regulations, and institutional reports. Data were analyzed using content and thematic analysis, with validity ensured through source and method triangulation. Results: The findings reveal three key dimensions of legal complexity: regulatory fragmentation caused by overlapping legal instruments and unclear institutional authority; coordination challenges arising from BP3MI’s dual role as regulator and service provider; and limited access to justice for migrant workers due to inadequate legal awareness and ineffective complaint mechanisms.Conclusions: Strengthening migrant worker protection requires regulatory harmonization, improved inter-agency coordination, more effective law enforcement, and greater legal empowerment. Reform efforts should prioritize clarifying institutional functions and simplifying the legal framework governing migrant worker deployment.Limitations: The study is limited by its qualitative design, relatively small sample size, and focus on selected regions and the pre-departure stage.Contributions: This study contributes to migration governance scholarship by combining normative legal analysis with empirical evidence and offers practical recommendations for improving migrant worker protection.